Observation of > 5 wt % zinc at the Kimberley outcrop, Gale crater, Mars. Issue 3 (12th March 2016) - Lasue, J.; Clegg, S. M.; Forni, O.; Cousin, A.; Wiens, R. C.; Lanza, N.; Mangold, N.; Le Deit, L.; Gasnault, O.; Maurice, S.; Berger, J. A.; Stack, K.; et al.
Abstract: Zinc‐enriched targets have been detected at the Kimberley formation, Gale crater, Mars, using the Chemistry Camera (ChemCam) instrument. The Zn content is analyzed with a univariate calibration based on the 481.2 nm emission line. The limit of quantification for ZnO is 3 wt % (at 95% confidence level) and 1 wt % (at 68% confidence level). The limit of detection is shown to be around 0.5 wt %. As of sol 950, 12 targets on Mars present high ZnO content ranging from 1.0 wt % to 8.4 wt % (Yarrada, sol 628). Those Zn‐enriched targets are almost entirely located at the Dillinger member of the Kimberley formation, where high Mn and alkali contents were also detected, probably in different phases. Zn enrichment does not depend on the textures of the rocks (coarse‐grained sandstones, pebbly conglomerates, and resistant fins). The lack of sulfur enhancement suggests that Zn is not present in the sphalerite phase. Zn appears somewhat correlated with Na2 O and the ChemCam hydration index, suggesting that it could be in an amorphous clay phase (such as sauconite). On Earth, such an enrichment would be consistent with a supergene alteration of a sphalerite gossan cap in a primary siliciclastic bedrock or a possible hypogene nonsulfide zinc deposition where Zn, Fe, Mn would have been transported in a reduced sulfur‐poor fluid and precipitated rapidly in the form of oxides. Key Points: Zinc‐enriched targets have been detected at the Kimberley outcrop using ChemCam A dedicated database and model have been developed for quantification Possible origin: supergene sphalerite gossan cap alteration or hypogene nonsulfide zinc deposition